Uji Eksperimental Pengaruh Panjang Chord Sudu Terhadap Kinerja Turbin Angin Sumbu Vertikal - Eva Hertnacahyani Herraprastanti; Muhamad Najib Mubarok; Sarip Sarip; Hendri Suryanto (Jurnal Teknik Mesin, 2020)
Indonesia's petroleum production continues to decline while energy demand continues to grow. As a result, there was an increase in imports of crude oil and imports of fuel oil products. The government issued a number of policies to reduce fuel use. One of the efforts is to manage renewable energy power plants such as wind energy. The wind turbine is a windmill that is used to generate electricity. The basic principle of working of a wind turbine is to convert wind energy into mechanical energy at the mill, then the rotation of the mill is used to rotate the generator which will produce electricity. One of the things that need to be considered in designing wind turbine blades is the size (radius of the rotor), airfoil section, chord length, and blade pitch angle. The blade chord length is the length of the straight line connecting the front and rear edges of the turbine blade. The purpose of this study was to determine the effect of blade chord length on the performance of a vertical axis wind turbine, including shaft rotation, wind power, generator power, rotor power, torque, Tip Speed ​​Ratio (TSR) and power coefficient. This research was conducted using a vertical axis wind turbine, with 4 L-type blades made of 60 mm thick aluminum plate, with variations in chord lengths of 140 mm, 170 mm, and 200 mm. From the results of the tests that have been carried out, it can be concluded that the chord length affects shaft rotation, wind power, generator power, rotor power, torque, Tip Speed ​​Ratio (TSR) and power coefficient.